Implementasi Model Pembelajaran Kooperatif Tipe Team Asissted Individualization Berbantuan Media Tutorial Meningkatkan Hasil Belajar PJOK Materi Shooting Free Throw Bola Basket - Ahmad, Afrizal Alanurdin; Wahjoedi, Wahjoedi; Wijaya, Made Agus (Universitas Pendidikan Ganesha, 2024)
This research aims to determine the learning outcomes of PJOK material on basketball free throw shooting through a team-assisted individualization type cooperative learning model assisted by tutorial media in class VII A students at SMP Negeri 1 Kabat Banyuwangi. This type of research is Classroom Action Research (PTK), carried out in two cycles, consisting of planning, implementing actions, observation or observations, and reflection. The subjects of this research were class VIIA students at SMP Negeri 1 Kabat, totaling 34 students consisting of (15 boys and 19 girls). Data collection was carried out in 3 aspects, namely affective, cognitive and psychomotor. The learning results in cycle I show that students' learning completeness is as follows: affective aspect 12%, cognitive aspect 24%, psychomotor 9%. Cycle II learning results in the affective aspect were 88%, cognitive aspect 91%, psychomotor aspect 85%. Based on the results of this research, it can be seen that basketball shooting learning outcomes increased from the implementation of the team assisted individualization type learning model assisted by tutorial media. This is known from the increase in the percentage of learning completeness in the average cycle value so that it is stated that through the implementation of the team assisted individualization type cooperative learning model assisted by tutorial media, it can improve the learning outcomes of class VIIA students at SMP Negeri 1 Kabat Banyuwangi.